Collaborating communities revisited - Dunsire, Gordon (Knjižnica, 2019)
Purpose: This article follows up "Collaborating communities: the RDA experience and its implications for common information environments", published in 2007 in the proceedings of the 11th seminar on Archives, Libraries, Museums held in Poreč, Croatia. That paper was written before the publication of RDA: Resource Description and Access, the successor to the Anglo-American Cataloguing Rules (AACR). The article outlines what has happened since, with a focus on the development of RDA in collaboration with related standards groups. Methodology/approach: This is a chronological review of the development of documents, which lead to the publication of RDA. Cooperation and harmonization of description of information objects among different concerned communities is also presented. Research limitations: The thorough review of RDA and related documents covers the period from 2008 to 2018. Originality/Practical implications: The strategic development of RDA is dependent on continuing collaboration with international communities, cultural heritage communities, and linked data communities. All of these communities have a strong interest in linked open data and the Semantic Web, and RDA has played a significant role in initiating and stimulating collaborative development of library and cultural heritage metadata in RDF format.
Keywords: 2008/2018; katalogizacija; katalogizacijska pravila; pravilniki; RDA